2002
DOI: 10.1007/s002200200653
|View full text |Cite
|
Sign up to set email alerts
|

Transformations RS 4 2 (3) of the Ranks ≤ 4¶and Algebraic Solutions of the Sixth Painlevé Equation

Abstract: Compositions of rational transformations of independent variables of linear matrix ordinary differential equations (ODEs) with the Schlesinger transformations (RS-transformations) are used to construct algebraic solutions of the sixth Painlevé equation. RS-Transformations of the ranks 3 and 4 of 2 × 2 matrix Fuchsian ODEs with 3 singular points into analogous ODE with 4 singular points are classified.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0
15

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(107 citation statements)
references
References 12 publications
1
91
0
15
Order By: Relevance
“…In the case β = 0, δ = 0 (or α = 0, γ = 0), the third Painlevé equation is a quadrature, and we exclude this case from the Painlevé family. D (1) j (j = 6, 7, 8) mean the affine Dynkin diagrams corresponding to Okamoto's initial value spaces. In this paper we omit the upper index (1) for simplicity and denote D 6 , D 7 , D 8 .…”
Section: Remarks On P3 and P5mentioning
confidence: 99%
“…In the case β = 0, δ = 0 (or α = 0, γ = 0), the third Painlevé equation is a quadrature, and we exclude this case from the Painlevé family. D (1) j (j = 6, 7, 8) mean the affine Dynkin diagrams corresponding to Okamoto's initial value spaces. In this paper we omit the upper index (1) for simplicity and denote D 6 , D 7 , D 8 .…”
Section: Remarks On P3 and P5mentioning
confidence: 99%
“…all isomonodromic deformations of the Fuchsian system are given by solutions to the Schlesinger equations (see, e.g., [36]) 1 . The solutions to the Schlesinger equations can be parameterized by the monodromy data of the Fuchsian system (1.2) (see precise definition below in Section 2).…”
Section: Introductionmentioning
confidence: 99%
“…This is a generalization of the celebrated Painlevé property of absence of movable critical singularities (see details in [14,15]). In certain cases the technique based on the theory of Riemann-Hilbert problem gives a possibility 1 Bolibruch constructed non-Schlesinger isomonodromic deformations in [4]. These can occur when the matrices A i are resonant, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work [4] it was shown that transformation RS 4 (4) generates quadratic transformation for the sixth Painlevé equation, in [5] a general notion of the RS-transformation for the so-called special functions of the isomonodromy type [6] were introduced and application to the construction of the algebraic solutions to the sixth Painlevé equation was discussed, in [7] we classified all RS 4 (3) transformations of the ranks ≤ 4.…”
Section: Introductionmentioning
confidence: 99%